Circular Economy Disclosure through Social Media: An Empirical Analysis on Twitter - Vitiana L'Abate; Nicola Raimo; Filippo Vitolla (Managing knowledge for sustainability, 2023)
In recent years, to solve the problems related to sustainability, there is an increasing need for a transition from linear production and consumption systems to new models oriented towards recycling, reuse, reuse and reuse. In the academic field, several scholars have turned their attention to the adoption by companies of the new circular economy models. Due to the interest of a large number of stakeholders in issues related to the circular economy, several scholars have begun to explore the circular economy disclosure practices of companies. Despite this, studies on the topic are still limited. The purpose of this study is firstly to examine the level of circular economy information disseminated through Twitter by companies and, secondly, to examine the impact of some characteristics of companies on the level of circular economy disclosure. Empirical results show that the most profitable and most indebted companies disclose a greater amount of circular economy information through their official Twitter accounts. This study contributes to enriching the academic literature and provides important practical contributions.
Keywords: 330